Efektivitas Permainan Roda Putar dalam Kemampuan Mengenal Angka pada Anak Usia 5-6 Tahun di Taman Kanak-kanak Mutiara Agam - Oktriana, Bella Isda; Yeni, Indra (Darul Yasin Al Sys, 2024)
The research purpose is to determine how well children at Mutiara Agam Kindergarten, ages 5-6, can recognize numbers when they utilize a spinning wheel. This research motivation is the fact that there are still many students who have not mastered the ability to count 10-20, which causes children's ability to recognize numbers 10-20 to not developThis kind of research is quantitative and employs quasi-experimental techniques. All of the students enrolled at Mutiara Agam Kindergarten served as the research population, and purposive sampling was used to choose the 15 students from each of the two classes, B1 and B2. Tests are used in the data gathering technique; these are five-point statements. Tests for normality, homogeneity, hypothesis, and effect size are used in data analysis procedures. The research results shown that the playing activity with a spinning wheel in the class for experimental had a significant influence compared to the controlled class with the activity of using number cards on the skill to recognize numbers in children at Mutiara Agam Kindergarten. With a sig (2-tailed) value of 0.00 < 0.05. The effect size test results obtained a d value of 0.98, which means that the d < 1 value is in the category in medium. Thus, it is conslussion that the activity of playing with a spinning wheel on the skill to recognize numbers in children aged 5-6 years at Mutiara Agam Kindergarten is effective.